Kediri Government Policy Before Year End Holiday Middle of the Covid-19 Pandemic - Megananta, Janatul Rona; Fauzi, Agus Machfud (NAJAHA, 2022)
All health protocol policies must be adhered to during the current pandemic. This is because the number of people who die every day is skyrocketing due to the Covid-19 virus. The aim of this research is to explain local government policies in dealing with the pandemic ahead of the year-end holidays. The method I use in this research is a qualitative approach, through direct observation and interviews with the people of Kresek Village, Tempurejo, Kediri City. The city government of Kediri has issued a policy, especially Large-Scale Social Restrictions (PSBB), namely a ban on leaving the house to celebrate year-end holidays. This policy is strictly enforced so that all residents do not leave the house to celebrate the year-end holidays. The Kediri City Government recommends that every village maintain security at each post. Uniquely, the sanctions given in each town are different. In the Tempurejo area, if people go out to celebrate the end of the year, they are sanctioned to go around the village for 8 rounds. There is also a policy that if they want to go out of town but do not bring a health certificate and a health certificate, they must spend the night in the Kelurahan, for approx. 8 hours for quarantine. This policy is an initiative of the RT/RW, Kelurahan and Covid-19 cluster, especially in Tempurejo Village, to support the Kediri City Government's Large-Scale Social Restrictions (PSBB) efforts in reducing mortality and Covid-19 during the year-end holidays in the Kediri City area.